Enhanced As(III) and As(V) Adsorption From Aqueous Solution by a Clay Based Hybrid Sorbent - Mudzielwana, Rabelani; Gitari, Mugera Wilson; Ndungu, Patrick (Frontiers in Chemistry, 2020)
In this study, a hybrid arsenic adsorbent was synthesized through intercalation inorganic and organic surfactant cations onto kaolin clay interlayers. The synthesized adsorbent was characterized X-ray fluorescence (XRF), Fourier Transform Infrared spectroscopy (FTIR), Scanning electron microscopy (SEM) and Brunauer-Emmett-Teller (BET). Batch studies were conducted to determine As(III) and As(V) removal capacity of hybrid sorbent synthesized. It is found that As(III) removal is optimum at pH range of 4-6 while As(V) removal is optimum at pH range 4-8. The data for adsorption kinetics fitted to pseudo second order model implying that adsorption of As(III) and As(V) is chemisorption. The isotherm studies showed a better fit to Langmuir isotherm model indicating that adsorption of both As(III) and As(V) occurred on a mono-layered surface. The maximum adsorption As(III) and As(V) capacity at room temperature as determined by Langmuir model were found to be 7.99 and 7.32 mg/g, respectively. Thermodynamic parameters, ∆Gᴼ and ∆Hᴼ were found to be negative indicating that adsorption process occurred spontaneously and exothermic. Inorgano-organo modified kaolin clay was successfully regenerated for up 7 adsorption-regeneration cycles using 0.01 M HCl as regenerant. This study concluded that hybrid sorbent synthesized in this study is suitable for arsenic removal from groundwater.